The Fractured Centre: Ecological Mimicry in Natalia García Freire’s This World Does Not Belong to Us: Pusat yang Retak: Mimikri Ekologis dalam “This World Does Not Belong to Us” Karya Natalia García Freire - Bhave, Abhidnya (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
Natalia Garcia Freire’s This World Does Not Belong To Us (2022) is an uncanny representation of the ecological haunting of Lucas and his father, engaging with colonial discourse and dispossession. This paper aims to examine how Freire’s novel deploys a paradigm of “ecological mimicry” by integrating Bhabha’s theory of colonial ambivalence and mimicry, extending Derrida’s concept of discourses and the instability of meaning. Both Derrida and Bhabha provide frameworks that reveal the instability of colonial discourse, which achieves its “origin” through the narration of repetition and difference. Employing a close reading and contextual postcolonial analysis, the paper examines how Lucas and his father perform colonial ambivalence as dispossessed subjects through ecological haunting and identification with nature. Extending Derrida and Bhabha’s theories rooted in discursive narratives, this study develops the concept of “ecological mimicry” to analyze Lucas’ resistance and resignification, deriving new meanings of identity and belonging. The analysis demonstrates the inversion and destabilization of colonial hierarchies through ecological mimicry. The study thus aims to contribute to postcolonial ecological criticism by expanding on Derrida and Bhabha’s frameworks into environmental narrative contexts.